Hypoxia induces melanotic pseudotumors in the larvae of mosquitoes of Culicidae family - Buchatskyi, L.P. (PH Akademperiodyka, 2023)
The melanotic pseudotumors in insects were predominantly studied in D. melanogaster. This fly has a phenomenon called “melanotic encapsulation”, which is formed as a result of the deposition of melanin grains in the form of pigmented masses on or near the surface of an embedded pathogen. In addition to melanin grains, these pigmented masses, as a rule, consist of clusters of adherent hemocytes, or various endogenous tissues encapsulated by these cells [1]. Up to the date, virtually no information on similar pseudotumor structures in blood-sucking mosquitoes has been reported. Our many-year field studies in natural habitats in the vicinity of Kyiv have demonstrated that in the larvae of blood-sucking mosquitoes of Culicidae family spawning from ovipositors kept under prolonged (6 months) hypoxia at the temperature about 0 °C, numerous small (50–80 µm) melanotic structures of a dark color resembling that in D. melanogaster have been revealed. In control larvae hatching in non-hypoxic conditions, such tumors were very rare. Most often, the symptoms were manifested in stage III–IV larvae, less often in younger stage larvae and pupae. Affected larvae became inactive, convulsively twitching when irritated. At the first stages of the disease, the fatty body and the dorsal parts of the segments of the chest and abdomen were weakly pigmented, later the separate spots of irregular shape appeared. An electron microscopic study of ultrathin sections of adipose body cells of affected larvae showed a large number of peculiar multilayer concentric membrane-like structures found in the cytoplasm, which have never been found in healthy mosquito larvae (Figure). In the immediate vicinity of such membranes, small spherical virus-like particles (VLP) about 30 nm in diameter were observed.